2019
DOI: 10.3390/pharmacy7030131
|View full text |Cite
|
Sign up to set email alerts
|

Improving Recruitment and Retention of Pharmacists in a Practice-Based Research Network

Abstract: Pharmacy practice-based research networks (PBRNs) are relatively new compared to their primary care forebears, representing a unique set of research challenges. Recruitment and retention of network members are essential to maintaining the integrity of the network and achieving its research goals. Many studies have evaluated recruitment and retention of practitioners to individual studies, while far fewer have reported on recruitment and retention to the network itself. This literature review summarizes current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In contrast, our CTR study showed 209 practitioners who enrolled patients; 195 (93%) continued participating for 3 years. The Network has achieved these high retention rates for clinical studies by drawing from its experiences and strategies cited in the literature [29][30][31]. The Network retains practitioners and patients by developing informal and professional relationships through continuous and positive communication and offers financial incentives to encourage their continued participation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our CTR study showed 209 practitioners who enrolled patients; 195 (93%) continued participating for 3 years. The Network has achieved these high retention rates for clinical studies by drawing from its experiences and strategies cited in the literature [29][30][31]. The Network retains practitioners and patients by developing informal and professional relationships through continuous and positive communication and offers financial incentives to encourage their continued participation.…”
Section: Discussionmentioning
confidence: 99%
“…Academic pharmacists could have roles in the conceptualisation of research, while the main role of practising pharmacists could relate to data collection in their workplace. Prior studies have reported that such research networks have been successfully established; [35][36][37] and this could also be considered for the Indonesian context. Secondly, the technical procedures for research should be integrated into the practitioner pharmacists' daily routine; this could help in reducing the additional burden related to research.…”
mentioning
confidence: 99%